LEGAL RECONSTRUCTION ON DOMESTIC RELATED PARTY TRANSACTIONS - Yudha Pramana (Scientia Integritas Utama, 2022)
It is necessary to conduct a juridical study to minimize the transfer of income or the basis of imposition of taxes and fees from one taxpayer to another, which can be engineered to reduce the total amount of tax payable on taxpayers who have speuniquelationships within the country. Based on distributive justice and corrective justice concepts and the hierarchy of laws and regulations (stafenbau theory). This article applies a normative juridical method with an evaluative and prescriptive thought. This method uses a positive legal inventory approach, an approach to legal principles, an approach to legal systematics, and a vertical and horizontal synchronization approach. Tax disputes related to unique relationships still occur. Even related parties’ transactions Domestic transactions are often complex business transactions between companies and their managers, directors, shareholders, or affiliates, making state tax revenues suboptimal. This paper requires an in-depth socio-legal research study, but this paper can enrich empirical research. This paper produces two novelties in the form of legal reconstruction. First, the rules for domestic-related transactions still rely on the arm's length principle (ALP), which is adequate to apply to cross-border transactions between related parties. Domestic special relationship transactions have their complexities. Second, there is a need for legal reconstruction of domestic related party transactions oriented towards increasing compliance (reporting certain transactions) and providing access to tax authorities in jointly taking responsibility for preventing and overcoming suboptimal state tax revenues.